Design and implementation of photovoltaic water pumping system - Ahmed Mustafa, Maiz Hadj (2014)
The solar photovoltaic system is considered as one of the most promising applications for a future sustainable supply power notably in remote areas where the electricity is unavailable or unreliable. Due to the continuous improvement of solar cell technology and the decrease in manufacturing cost, photovoltaic powered water pumps have received considerable attention in the last few years to satisfy the basic need for a large proportion of the world's rural population. This dissertation deals with the modeling and simulation of a photovoltaic water pumping system consisting of PV panel as a generator, power conditioning unit that constitutes of a buck-boost chopper and single phase full bridge inverter to feed a single phase induction motor actuating centrifugal pump. The pump feeds the water tank in order to use it when the sun is not shining. The simulation was carried out through MA TLAB/SIMULINK software using the equivalent electric circuit of each component for each subsystem then the overall system consisting of the subsystems shows the feasibility of the entire photovoltaic water pumping system. This research gives an emphasis on power electronic stage, a DC/DC buck boost chopper was designed and realized, showing its efficiency when connecting to the system. This work stresses on system sizing which is important in order to design a successful installation, HOMER software has been used to recognize the system sizing and it shows a high performance in term of sensitivity analysis of a wide range of input which may affect the system's behavior. The system sizing has been achieved reliably and economically through two criteria which are Annual Capacity Shortage (ACS) and Levelized Cost of Energy (LCE), the results could then serve as a starting point for the designing and optimizing of a successful installation. A prototype hardware of water pumping system which can be used for domestic purposes was built and tested, the experimental results were satisfactory.